Tropospheric ozone and its natural precursors impacted by climatic changes in emission and dynamics - Dewan, Surat; Lakhani, Anita (Frontiers in Environmental Science, 2022)
Climate change plus ozone pollution is a lethal combination that adversely affects human health, agriculture productivity, ecosystems, and the world economy. Currently, there is a growing concern that climate change may aggravate ozone pollution even after reducing anthropogenic precursor source activities. Part of it may be due to temperature-enhanced natural precursor emissions of ozone, increased stratospheric–tropospheric exchange of ozone, more frequent periods with meteorologically stagnant conditions favouring pollution build-up, changes in wetland methane emissions, and enhanced concentrations of atmospheric carbon dioxide. The quantification of climate change and ozone levels involves complex chemical, radiative, biogenic, and transport processes and feedback that are difficult to fully comprehend. Further, the fact that ozone is a short-lived climate forcer and a potent greenhouse gas provides a feedback loop and makes climate-ozone links even more multifaceted. This review examines the up-to-date understanding of the processes regulating tropospheric ozone from regional to global scales and the associated climate connections. We explore the recent findings in ozone precursor emissions from natural sources, ozone formation chemistry, its transport on hemispheric scales, future plausible ozone concentrations in different shared socioeconomic pathways, and changes in the radiative forcing of ozone. The review demonstrates the challenges and limitations associated with climate-ozone linkages and their incorporation in models, which are due to uncertainties in magnitude and signs of projected precursor emissions in response to future climate change and also due to the difference in models.